The Role of Satisfaction on Mediating The Effects of Easier Usage and Benefit Perceptions to The Loyalty of Brilink Agents in Denpasar City - Putu Arina Hermarani; Ni Wayan Ekawati; I Putu Gede Sukaatmadja; Putu Saroyini Piartrini (Publikasi Indonesia, 2024)
Seeing the unequal conditions of establishing access to bank services in certain areas, the Financial Services Authority (OJK) issued a program entitled Laku Pandai. BRI has the largest number of Laku Pandai agents, known as BRILink agents, compared to other bank agents. The purpose of this research is to discuss the role of satisfaction in mediating the influence of perceived ease of use and benefit perceptions on BRILink Agent loyalty. Benefit perception is the condition of a person who believes that using a certain technological system can improve his or her performance. Satisfaction is defined as the feeling of pleasure or disappointment that a person feels when obtaining performance results from a product or service. Loyalty can be described as a continuous process of establishing repeat purchasing relationships over the long term. This research is a type of quantitative research that is associative in nature. The population of this research is BRILink agents located in Denpasar City. The sampling technique used purposive sampling with a sample size of 100 people. Data collection was carried out through a survey using a research instrument in the form of a questionnaire. The results of this research can provide an empirical contribution regarding the relationship between the variables of perceived ease of use, benefit perceptions, satisfaction, and loyalty for the development of consumer behavior theory. BRI Denpasar Branch management can improve the ease of operating technology on BRILink services.